2016
DOI: 10.1186/s12887-016-0729-0
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns of early childhood and maternal socioeconomic status in a unique prospective sample from a randomized controlled trial of Prenatal DHA Supplementation

Abstract: BackgroundDietary habits established in early childhood and maternal socioeconomic status (SES) are important, complex, interrelated factors that influence a child’s growth and development. The aim of this study was to define the major dietary patterns in a cohort of young US children, construct a maternal SES index, and evaluate their associations.MethodsThe diets of 190 children from a randomized, controlled trial of prenatal supplementation of docosahexaenoic acid (DHA) were recorded at 6-mo intervals from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…Financial support is another important factor frequently associated with DP in children. A systematic review conducted by Bazzano et al [59] showed available qualitative research on DPs and practices in infants and young children from the perspective of parents and families in low-income settings in the USA. This review reported four categories of barriers obstructing recommended breastfeeding practices such as lack of support for breastfeeding from families, health workers and due to time poverty, and three categories of barriers to recommended complementary feeding practices showing how higher quality foods were replaced with lower quality foods for financial reasons, lack of diversity in available foods, lack of water for cooking, and inability to buy food.…”
Section: Discussionmentioning
confidence: 99%
“…Financial support is another important factor frequently associated with DP in children. A systematic review conducted by Bazzano et al [59] showed available qualitative research on DPs and practices in infants and young children from the perspective of parents and families in low-income settings in the USA. This review reported four categories of barriers obstructing recommended breastfeeding practices such as lack of support for breastfeeding from families, health workers and due to time poverty, and three categories of barriers to recommended complementary feeding practices showing how higher quality foods were replaced with lower quality foods for financial reasons, lack of diversity in available foods, lack of water for cooking, and inability to buy food.…”
Section: Discussionmentioning
confidence: 99%
“…Other details of study design and demographic characteristics were included in a report of pregnancy outcome. 6 Information on childhood diet 8 and 5-year body composition of the offspring 9 has also been reported.…”
Section: Methodsmentioning
confidence: 99%
“…We adjusted for maternal rather than paternal education as the mother in most cases was the primary caretaker. Moreover, studies have found that low maternal education influences different aspects of offspring dietary intake [29,30] and predicts childhood obesity [31]. The same set of analyses was also conducted for maternal and paternal HCC, following the same adjustment scheme, but with added information on parental BMI and paternal education in analyses of the fathers HCC.…”
Section: Methodsmentioning
confidence: 99%